Faktor-faktor yang mempengaruhi perilaku seksual pada remaja di Posyandu Remaja Desa Sukarami Kecamatan Belitang Kabupaten OKU Timur - devi, devi; Arif, Ahmad; Riski, Meriska (NHM PRESS, 2023)
One of the prevailing reproductive health issues is unintended pregnancies. According to the World Health Organization (WHO) in 2016, adolescent girls aged 15–19 in developing countries experienced unintended pregnancies at a rate of (49%). The rise in cases of adolescents engaging in unprotected sexual activity, as reported by KPAI and the Ministry of Health in 2017, revealed that 62.7% of Indonesian adolescents had engaged in sexual activity. This study aims to comprehensively understand the combined influence of knowledge, parental roles, peer influence, and exposure to social media on adolescent sexual behavior at the Youth Health Project Center in Sukarami Village, Sub-district Belitang, East OKU Regency in 2023. The research adopts a quantitative approach, utilizing an analytical survey method with a cross-sectional design. The study population encompasses all adolescents aged 10 to 18 within the operational area of Sukarami Village Youth Health Project Center, totaling 240 individuals. A sample size of 70 respondents was utilized. Univariate analysis of the 70 respondents revealed that 14 respondents (20.0%) exhibited risky sexual behavior, while 56 respondents (80.0%) did not. The statistical chi-square test yielded ρ values of 0.002 for the knowledge variable, 0.004 for the parental role variable, 0.005 for the peer influence variable, and 0.010 for the social media exposure variable. All ρ values were below α=0.05, indicating significant correlations between knowledge, parental roles, peer influence, and social media exposure with risky sexual behavior at the Youth Health Project Center in Sukarami Village, Sub-district Belitang, East OKU Regency in 2023.